Availability of Illegal Drugs During the COVID-19 Pandemic in Western Germany - Scherbaum, Norbert; Bonnet, Udo; Hafermann, Henning; Schifano, Fabrizio; Bender, Stefan; Grigoleit, Torsten; Kuhn, Jens; Nyhuis, Peter; Preuss, Ulrich W.; Reymann, Gerhard; Schneider, Udo; Shibata, Jo; et al. (Frontiers in Psychiatry, 2021)
Background: In response to the COVID-19-pandemic, a lockdown was established in the middle of March 2020 by the German Federal Government resulting in drastic reduction of private and professional travelling in and out of Germany with a reduction of social contacts in public areas. Research questions: Did the lockdown lead to a reduced availability of illegal drugs? In consequence, did subjects with substance-related problems try to cope with possible drug availability issues whilst increasingly obtaining drugs via the internet? Did they replace their preferred illegal drug with by novel psychoactive substances, including new synthetic opioids? Methods: A questionnaire was anonymously filled in by subjects with substance-related disorders, typically attending low-threshold settings; drug consumption facilities; and inpatient detoxification wards from a range of locations in the Western part of Germany. Participants had to both identify their main drug of abuse and to answer questions regarding its availability, price, quality, and routes of acquisition. Results: Data were obtained from 362 participants. The most frequent main substances of abuse were cannabis (n=109), heroin (n=103), and cocaine (n=75). A minority of participants reported decreased availability (8.4%), increased price (14.4%), or decreased quality (28.3%) of their main drug. About 81% reported no change in their drug consumption due to the COVID-19 pandemic and the lockdown. A shift to the use of novel psychoactive substances including new synthetic opioids were reported only by single subjects. Only 1-2% of the participants obtained their main drug via the web. Discussion: Current findings may suggest that recent pandemic-related imposed restrictions may have not been able to substantially influence both acquisition and consumption of drugs within a context of polydrug, including opiates, users attending a range of addiction services in Germany.